Melawan Gus Dur - Anwar, Fuad 1958- (Pustaka Tokoh Bangsa Distribusi, LKiS Pelangi Aksara, 2004)
Criticism towards Abdurrahman Wahid's political thought by members of Nahdlatul Ulama, a Muslim organization in Indonesia.